Uporaba bioloških zdravil za zdravljenje očesnih vnetij - Vidović Valentinčič, Nataša (Zdravniški vestnik, 2012)
Purpose of review: The paper summarizes the available studies on the use, efficacy, and safety of biologic agents in the treatment of ocular inflammation. Methods: Presentation of the use of biologic agents for the treatment of ocular inflammation, with special emphasis on our experience. Results: Biologic agents were used in 12 patients treated for noninfectious uveitis/scleritis in the last 5 years. Ocular inflammatory disease was part ofsystemic autoimmune disease in 11 patients, in one the systemic disease was not established. The efficacy of biologics was good in all patients, there were less relapses of ocular disease and visual acuity was stable. The reactivation of pulmonary tuberculosis and herpetic uveitis occurred in one patient each. Summary: Biologic therapies, especially anti- TNF-Ž factor agents in the last years and interferons show a high efficacy in controlling noninfectious uveitis and scleritis, resistant to standard immunosuppressants.So far, our experiences with the use of biologics in our patients are good, but high costs and limited long-term experience restrict their use.
Keywords: biološka zdravila; imunosupresivno zdravljenje; skleritis; uveitis; zaviralci TNF-a